Emerging targeted and cellular therapies in the treatment of advanced and metastatic synovial sarcoma - Fuchs, Joseph R.; Schulte, Brian C.; Fuchs, Jeffrey W.; Agulnik, Mark (Frontiers in Oncology, 2023)
Synovial sarcoma is a soft tissue sarcoma accounting for approximately 1,000 cases per year in the United States. Currently, standard treatment of advanced and metastatic synovial sarcoma is anthracycline based chemotherapy. While advanced synovial sarcoma is more responsive to chemotherapy compared to other soft tissue sarcomas, survival rates are poor, with a median survival time of less than 18 months. Enhanced understanding of tumor antigen expression and molecular mechanisms behind synovial sarcoma provide potential targets for treatment. Adoptive Cell Transfer using engineered T-cell receptors is in clinical trials for treatment of synovial sarcoma, specifically targeting New York esophageal squamous cell carcinoma-1 (NY-ESO-1), preferentially expressed antigen in melanoma (PRAME), and melanoma antigen-A4 (MAGE A4). In this review, we explore the opportunities and challenges of these treatments. We also describe artificial adjuvant vector cells (aAVCs) and BRD9 inhibitors, two additional potential targets for treatment of advanced synovial sarcoma. This review demonstrates the progress that has been made in treatment of synovial sarcoma and highlights the future study and qualification needed to implement these technologies as standard of care.